2016
DOI: 10.5694/mja15.01153
|View full text |Cite
|
Sign up to set email alerts
|

Comparing colorectal cancer treatment and survival for Aboriginal and non‐Aboriginal people in New South Wales

Abstract: Objectives: Our aim was to compare surgical treatment rates and survival rates for Aboriginal and non‐Aboriginal people in New South Wales with colorectal cancer, and to describe the medical treatment received by a sample of Aboriginal people with colorectal cancer. Design, setting and participants: All people diagnosed with colorectal cancer in NSW during 2001–2007 were identified and their cancer registry records linked to hospital admissions data and death records. A medical records audit of a sample of Abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…For bowel cancer, our results strengthen findings from an earlier population‐based study in NSW that found similar surgery rates between Aboriginal and non‐Aboriginal bowel cancer patients during 2001–2007 14 . That study reported that adjuvant chemotherapy and radiotherapy use for Aboriginal people, based on a medical record review of a sample of Aboriginal people diagnosed 2001–2010 ( n = 145), was the same as that reported in NSW population‐based treatment pattern surveys.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For bowel cancer, our results strengthen findings from an earlier population‐based study in NSW that found similar surgery rates between Aboriginal and non‐Aboriginal bowel cancer patients during 2001–2007 14 . That study reported that adjuvant chemotherapy and radiotherapy use for Aboriginal people, based on a medical record review of a sample of Aboriginal people diagnosed 2001–2010 ( n = 145), was the same as that reported in NSW population‐based treatment pattern surveys.…”
Section: Discussionsupporting
confidence: 86%
“…In New South Wales (NSW), Aboriginal people were less likely to receive surgery than non‐Aboriginal people for non‐metastatic non‐small cell lung cancer, 13 breast cancer 8 and localised or regional prostate cancer 9 . Similar surgery rates were observed between Aboriginal and non‐Aboriginal people for colorectal cancer 14 . Cancer treatment can be complex, requiring consultation with specialists and treatment in specialist centres.…”
Section: Introductionmentioning
confidence: 97%
“…Câncer colorretal está entre as principais causas de óbito em populações nativas de países desenvolvidos 31,58,59,60,61 . Disparidades étnicas traduzidas em diagnóstico tardio e pior sobrevida desse câncer foram observadas entre indígenas em comparação a populações não indígenas 62,63,64,65 . No presente estudo, a maior mortalidade entre homens indígenas, tendo como referência a população masculina do Acre e da Região Norte, sugere menor acesso ao diagnóstico e tratamento precoce da doença.…”
Section: Discussionunclassified
“…[17][18][19] Aboriginal and Torres Strait Islander people in Australia (respectfully referred to here as Indigenous Australians) comprise 3% of the total Australian population, 20 and experience socioeconomic and health disparities. [18][19][20]23,26,27 In Australia, the availability of health services generally decreases with increase in remoteness. 22 Compared with mainstream Australia, they experience marked disparities in cancer mortality 23 and survival, 18,19,24 which are largely attributed to being diagnosed later, 18,19,25 receiving less treatment 18,19 and experiencing higher rates of comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…22 Compared with mainstream Australia, they experience marked disparities in cancer mortality 23 and survival, 18,19,24 which are largely attributed to being diagnosed later, 18,19,25 receiving less treatment 18,19 and experiencing higher rates of comorbidities. [18][19][20]23,26,27 In Australia, the availability of health services generally decreases with increase in remoteness. [28][29][30] As a higher proportion of Indigenous Australians live in rural areas, 20 together with other Australians they have worse cancer outcomes than those living in major cities.…”
Section: Introductionmentioning
confidence: 99%